2015
DOI: 10.1128/ec.00053-15
|View full text |Cite
|
Sign up to set email alerts
|

Auxotrophic Mutations Reduce Tolerance of Saccharomyces cerevisiae to Very High Levels of Ethanol Stress

Abstract: Very high ethanol tolerance is a distinctive trait of the yeast Saccharomyces cerevisiae with notable ecological and industrial importance. Although many genes have been shown to be required for moderate ethanol tolerance (i.e., 6 to 12%) in laboratory strains, little is known of the much higher ethanol tolerance (i.e., 16 to 20%) in natural and industrial strains. We have analyzed the genetic basis of very high ethanol tolerance in a Brazilian bioethanol production strain by genetic mapping with laboratory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It was also reported that heterozygous deletion of MET4 caused hypersensitivity to H 2 O 2 and decreased oxidative stress resistance [88]. In addition, the presence of auxotrophic mutations has been linked to reduced stress tolerance in yeast [89,90].…”
Section: Discussionmentioning
confidence: 98%
“…It was also reported that heterozygous deletion of MET4 caused hypersensitivity to H 2 O 2 and decreased oxidative stress resistance [88]. In addition, the presence of auxotrophic mutations has been linked to reduced stress tolerance in yeast [89,90].…”
Section: Discussionmentioning
confidence: 98%
“…While nutritional supplementation may differ from genetic complementation, the difference could be minimal when YB526 and YB332 were cultured in the complex media under the same conditions. Previous reports suggested that the great differences between the prototrophic and auxotrophic strains could be led to only by severe nutrient starvation or very high levels of ethanol stress (16-20%) [36,37]. And two major responses from the nutrient starvation were demonstrated previously as follows: (1) down-regulation of processes linked to cell growth and catabolism and (2) activation of carbon or nitrogen metabolic pathways for the supply of auxotrophically required compound [37].…”
Section: Rna-seq Transcriptomics Analysis Of Faa Mutant Yb526 Comparementioning
confidence: 95%
“…cerevisiae , functional analysis showed that disruption of LEU2 resulted in Leu-auxotroph and decreased resistance to acetic acid and to very high levels of ethanol stress of the mutants [7]. Very few documents characterized functions of LEU2 in filamentous fungi except for a relatively ancient and primary research in Aspergillus niger showed that this fungus elaborates two isoenzymes of IPMD and these two encoding genes were differentially expressed [8].…”
Section: Introductionmentioning
confidence: 99%